The outdoor classroom : ages 3-7 : using ideas from Forest Schools to enrich learning - Constable, Karen, ....-; Green, Sandy, ....- (London : Routledge, 2012)
This book clearly explains the learning potential of the outdoor environment and practically demonstrates how the ‘Outdoor Classroom' can be developed in early years settings and schools. Drawing on the Forest School approach, it aims to inspire practitioners to think creatively about their outside area and how they can provide rich play opportunities for children that will further their learning regardless of any time, space or financial restraints.